The role of the primary motor cortex in motor imagery: A theta burst stimulation study. (3rd May 2022) - Barhoun, Pamela; Fuelscher, Ian; Do, Michael; He, Jason L.; Cerins, Andris; Bekkali, Soukayna; Youssef, George J.; Corp, Daniel; Major, Brendan P.; Meaney, Dwayne; Enticott, Peter G.; Hyde, Christian
Abstract: While mentally simulated actions activate similar neural structures to overt movement, the role of the primary motor cortex (PMC) in motor imagery remains disputed. The aim of the study was to use continuous theta burst stimulation (cTBS) to modulate corticospinal activity to investigate the putative role of the PMC in implicit motor imagery in young adults with typical and atypical motor ability. A randomized, double blind, sham‐controlled, crossover, offline cTBS protocol was applied to 35 young adults. During three separate sessions, adults with typical and low motor ability (developmental coordination disorder [DCD]), received active cTBS to the PMC and supplementary motor area (SMA), and sham stimulation to either the PMC or SMA. Following stimulation, participants completed measures of motor imagery (i.e., hand rotation task) and visual imagery (i.e., letter number rotation task). Although active cTBS significantly reduced corticospinal excitability in adults with typical motor ability, neither task performance was altered following active cTBS to the PMC or SMA, compared to performance after sham cTBS. These results did not differ across motor status (i.e., typical motor ability and DCD). These findings are not consistent with our hypothesis that the PMC (and SMA) is directly involved in motor imagery. Instead, previous motor cortical activation observed during motor imagery may be an epiphenomenon of other neurophysiological processes and/or activity within brain regions involved in motor imagery. This study highlights the need to consider multi‐session theta burst stimulation application and its neural effects when probing the putative role of motor cortices in motor imagery. Abstract : A controlled continuous theta burst stimulation protocol was adopted to examine the role of the primary motor cortex in motor imagery. While corticospinal excitability was suppressed in individuals with typical motor ability, no changes in imagery performance were detected after applying active stimulation to the motor regions. This suggests that motor regions may not be causally implicated in motor imagery and/or that multiple stimulation sessions may be required when inducing cognitive‐behavioral changes.